Implementasi Kebijakan Retribusi Pelayanan Tera Ulang Sebagai Strategi Peningkatan Pendapatan Asli Daerah (Pad) Di Kabupaten Lombok Barat - Muhammad Tahir; Nasruddin Nasruddin; Mey Susanti AS (Journal of Government and Politics (JGOP), 2021)
The West Lombok Regency Government issued Regional Regulation Number 5 of 2018 concerning Retribution for Calibrated / Recalibrated Services, which regulates the implementation of metrological activities in West Lombok Regency, in this case carried out by the West Lombok Regency Industry and Trade Service, as well as to explore the maximum potential of the tools. uttp which is in the West Lombok region and will later become a source of regional revenue (PAD) through the collection of re-calibrated service fees. The purpose of this study is to provide an overview of the implementation of a re-calibrated service charge policy in increasing local revenue in West Lombok Regency. This study uses a descriptive qualitative study to explain the implementation of a re-calibrated service retribution policy in increasing local revenue in West Lombok Regency. The results showed that the implementation of the retribution policy for recalibrating services was quite good, but it could not reach all areas of West Lombok Regency, all of this was due to resource factors, namely the lack of rightful staff, metrological supervisors and PPNS metrology. This is in accordance with George C. Edwards III's (1980) Implementation Theory, namely the four factors / variables of the success of the implementation process, namely communication, resources, disposition and organization.